Clinically insignificant trunnionosis in large-diameter metal-on-polyethylene total hip arthroplasty. Issue 1 (January 2017) - Hothi, H. S.; Kendoff, D.; Lausmann, C.; Henckel, J.; Gehrke, T.; Skinner, J.; Hart, A.
Abstract : Objectives: Mechanical wear and corrosion at the head-stem junction of total hip arthroplasties (THAs) (trunnionosis) have been implicated in their early revision, most commonly in metal-on-metal (MOM) hips. We can isolate the role of the head-stem junction as the predominant source of metal release by investigating non-MOM hips; this can help to identify clinically significant volumes of material loss and corrosion from these surfaces. Methods: In this study we examined a series of 94 retrieved metal-on-polyethylene (MOP) hips for evidence of corrosion and material loss at the taper junction using a well published visual grading method and an established roundness-measuring machine protocol. Hips were retrieved from 74 male and 20 female patients with a median age of 57 years (30 to 76) and a median time to revision of 215 months (2 to 324). The reasons for revision were loosening of both the acetabular component and the stem (n = 29), loosening of the acetabular component (n = 58) and infection (n = 7). No adverse tissue reactions were reported by the revision surgeons. Results: Evidence of corrosion was observed in 55% of hips. The median Goldberg taper corrosion score was 2 (1 to 4) and the annual rate of material loss at the taper was 0.084 mm 3 /year (0 to 0.239). The median trunnion corrosion score was 1 (1 to 3). Conclusions: We have reported a level of trunnionosis for MOP hips with large-diameter heads that were revised for reasons other than trunnionosis, and therefore may be clinically insignificant. Cite this article : H. S. Hothi, D. Kendoff, C. Lausmann, J. Henckel, T. Gehrke, J. Skinner, A. Hart. Clinically insignificant trunnionosis in large-diameter metal-on-polyethylene total hip arthroplasty. Bone Joint Res 2017;6:52–56. DOI: 10.1302/2046-3758.61.BJR-2016-0150.R2.